ANALISIS KEPUASAN DOSEN DAN MAHASISWA TERHADAP KINERJA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR UNIVERSITAS PAKUAN - Nurlinda Safitri; Nedin Badruzzaman; Elly Sukmanasa (Universitas Pakuan, 2020)
ANALYSIS OF SATISFACTION OF LECTURERS AND STUDENTS ON THE PERFORMANCE OF ELEMENTARY TEACHER EDUCATION STUDY PROGRAMS, UNIVERSITY OF PAKUAN.The quality of educational institutions is strongly influenced by input from various factors that influence it, including leadership policy factors, facilities supporting the teaching and learning process. The performance of study programs is one of the most important benchmarks of the success of education in a tertiary institution because it will determine the high or low quality of education in tertiary institutions. Lecturers and students often complain about the policies implemented by study programs, especially about the facilities and facilities in the classroom that are not good so that the learning process becomes less conducive. The impact of the problem about dissatisfaction on the performance of the study program is shown by its uncomfortable learning behavior. The purpose of this study is to find out how the study program performance is assessed by lecturers and students, and to find out what indicators of lecturer and student satisfaction have been carried out by Elementary Teacher Education (PGSD) Study Programs. To analyze the satisfaction of lecturers and students on the performance of PGSD Study Programs with qualitative methods with descriptive designs. The results showed that lecturers and students' satisfaction with PGSD Study Programs services was in the quite satisfied range. In general, students felt quite satisfied with PGSD Study Programs services. Students feel quite satisfied with tangible aspects, reliability, assurance, and empathy. The study program performance was responded to very satisfied by lecturers and students. In general, lecturers and students are quite satisfied with the service performance of PGSD Study Programs, but there are still some indicators that still require the attention of PGSD Study Programs, especially in the tangible, reliability, assurance, and empathy aspects.